2022
DOI: 10.1186/s12944-021-01621-7
|View full text |Cite
|
Sign up to set email alerts
|

High remnant cholesterol level is relevant to diabetic retinopathy in type 2 diabetes mellitus

Abstract: Background Diabetic retinopathy (DR) is the primary oculopathy causing blindness in diabetic patients. Currently, there is increasing interest in the role of lipids in the development of diabetic retinopathy, but it remains controversial. Remnant cholesterol (RC) is an inexpensive and easily measurable lipid parameter; however, the relationship between RC and DR in type 2 diabetes mellitus (T2DM) has not been elucidated. This research investigates the relevance between RC levels and DR severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
0
22
3
Order By: Relevance
“…Elevated cholesterol remnants have recently been reported as a potential risk factor for DR in T2D subjects [ 58 ]; however, we did not observe elevations in the serum concentrations of this lipoprotein class in our T2D subjects with DR. The reason for the inconsistent results between the former study and our data is currently unknown, but it could be partly explained by the different approaches used to estimate the remnant cholesterol concentrations in each study.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Elevated cholesterol remnants have recently been reported as a potential risk factor for DR in T2D subjects [ 58 ]; however, we did not observe elevations in the serum concentrations of this lipoprotein class in our T2D subjects with DR. The reason for the inconsistent results between the former study and our data is currently unknown, but it could be partly explained by the different approaches used to estimate the remnant cholesterol concentrations in each study.…”
Section: Discussioncontrasting
confidence: 91%
“…The reason for the inconsistent results between the former study and our data is currently unknown, but it could be partly explained by the different approaches used to estimate the remnant cholesterol concentrations in each study. In this respect, our NMR analysis provided a more accurate estimation of serum cholesterol remnant concentrations than that used in the previous studies [ 56 , 58 ], which simply consisted of subtracting the LDL-C and HDL-C moieties from Total-C. Like in the case of T1D, IDL lipids did not contribute to improving predicting DR in our cohort of subjects with T2D.…”
Section: Discussionmentioning
confidence: 85%
“…In a cross-sectional study including 456 Chinese with type 2 diabetes, Shan et al found that RC levels were positively associated with DR risk [ 2 ]. At the same time, the prevalence of DR in their study was 47.59%, whereas it was 35.13% in our study [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipids are risk factors for macrovascular disease. According to some recent studies, conventional serum lipid levels such as total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-c), and high-density lipoprotein cholesterol (HDL-c) were not significantly associated with DR [ 2 , 3 ]. Remnant cholesterol (RC) is the cholesterol content of triglyceride-rich lipoproteins, which are very-low-density lipoprotein (VLDL) and intermediate-density lipoprotein (IDL) in the fasting state and the non-fasting state chylomicron remnants [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation